Development and Characterization of a Semi-Solid Dosage Form of Meglumine Antimoniate for Topical Treatment of Cutaneous Leishmaniasis - Diana Berenguer; Lilian Sosa; Magdalena Alcover; Marcella Sessa; Lyda Halbaut; Carme Guillén; Roser Fisa; Ana Cristina Calpena-Campmany; Cristina Riera (MDPI AG, 2019)
Cutaneous leishmaniasis (CL) is treated with painful intralesional injections of meglumine antimoniate (MA). With the aim of developing an alternative topical treatment for CL, a gel-based formulation with 30% MA was prepared and its physicochemical properties, stability and rheological behavior were studied. The following were assessed: drug release on propylene hydrophilic membranes ex vivo human skin permeation, tolerance in healthy volunteers, cytotoxicity in three cell lines and anti-leishmanial activity against Leishmania infantum promastigotes and amastigotes. The MA gel formulation was found to have suitable pH, and good spreadability and stability. Low quantities of pentavalent antimony (SbV) were observed in release and permeation tests, whereas retention was high in both non-damaged and damaged skin (71,043.69 ± 10,641.57 and 10,728 ± 2254.61 µg/g/cm2 of SbV, respectively). The formulation did not have a toxic effect on the cell lines, and presented lower SbV IC50 values against amastigotes (15.76 ± 4.81 µg/mL) in comparison with the MA solution. The high amount of drug retained in the skin and the SbV IC50 values obtained suggest that this semi-solid dosage form has potential as an alternative treatment of CL.